Salinity Monitoring and Modelling at Different Scales: An Editorial Overview - Mohammad Farzamian; Maria Conceição Gonçalves; Tiago B. Ramos (Land)
Soil salinization is a significant abiotic process affecting arid, semi-arid, and sub-humid regions worldwide [...]